Analysis of original bis-arylazaazkanes derivatives compliance with the calculated pharmacophoric models of biaromatic ligands of cardioprotective drugs biotargets - G. V. Mokrov; A. S. Pantileev; T. Yu. Vorobieva; V. E. Biryukova; S. A. Kryzhanovskii; V. L. Dorofeev (LLC "Publisher OKI", 2024)
Eight important biotargets of biaromatic cardioprotective drugs were selected in this work: calcium Cav1.2-channel, sodium Nav1.5-channel, potassium hERG-channel and Kv1.5-channel, HCN-channel, β1-adrenergic receptor, ryanodine RyR2-receptor and σ1-receptor. Biaromatic ligands databases were collected for each of them, on the basis of which their pharmacophore models were calculated in the Phase Schrödinger program. Using the PhaseScore function, we analyzed the correspondence of previously synthesized and studied bis-arylazaazlkanes to calculated pharmacophore models. It was found that the vastmajority of molecules have a correspondence of more than 50 % to all models, which indicates a high probability of the involvement of these biotargets in the possible cardioprotective effects of bis-arylazaazlkanes, and also confirms the hypothesis of the multitargetability of substances with this structure.